Ƒ(x) = x2 + 2x − 15 to find the solution when ƒ(x) = 0.
2 answers:
Answer:
Step-by-step explanation:
<u>Step 1: Set the equation to 0</u>
<u />
<u>Step 2: Factor</u>
<u />
<u>Step 3: Solve for x</u>
<u />
Answer:
Answer:
f = 2 + -15x-1 + x
Step-by-step explanation:
Simplifying
f(x) = x2 + 2x + -15
Multiply f (x)
fx = x2 + 2x + -15
Reorder the terms:
fx = -15 + 2x + x2
Solving
fx = -15 + 2x + x2
Solving for variable 'f'.
Move all terms containing f to the left, all other terms to the right.
Divide each side by 'x'.
f = -15x-1 + 2 + x
Simplifying
f = -15x-1 + 2 + x
Reorder the terms:
f = 2 + -15x-1 + x
You might be interested in
Answer:
Y = x^2/2 - 2x - 2
Step-by-step explanation:
Answer: Check if numbers are prime. Composite numbers prime factorization (decomposing, breaking numbers down to prime factors). Inscribe them as a product of prime factors, in exponential notation.
Answer: 3=24/8 24/8 - 1/8 = 23/8 or 2 7/8
Step-by-step explanation:
Exchange 3 into 24/8 which is still 3 but in 8th’s. Then subtract 1/8 from 24/8 which is 23/8 or 2 7/8
Answer:
p ositive skewed
this is correct.
Subtract 84 on the other side of the equal sign and bring down c and the answer you get from 111 - 84.